Transesterification of Coconut Oil Using Dimethyl Carbonate and TiO2/SiO2 Heterogeneous Catalyst - Kamisah D. Pandiangan; Wasinton Simanjuntak (Indonesian Journal of Chemistry, 2013)
In this study, transesterification of coconut oil with dimethyl carbonate (DMC) for preparing biodiesel has been studied using TiO2/SiO2 as heterogeneous catalyst, with the main purpose to investigate the effect of molar ratio of DMC to oil. The product was analyzed by GC-MS to identify the fatty acid methyl esters (FAMEs) composting the biodiesel. The significant role of the DMC to oil ratio was observed in this study, in which the oil conversion was found to increase with increasing molar ratio of DMC : Oil, with the highest percent of conversion of 88.44%. The GC-MS analysis revealed the presence of methyl esters in accordance with the composition of coconut oil commonly reported. Formation of FAMEs was verified by 1H-NMR spectroscopic analysis, which also suggested that some of the fatty acids remain unconverted into biodiesel. The biodiesel produced was found to have kinematic viscosity of 2.4 mm2/S at 40 °C, flash point of 103 °C, and cetane number of 54.